Realização pessoal na experiência comunitária em alcoólicos anônimos: uma pesquisa fenomenológica - Ana Claudia Bernardes Guimaraes (2014)
The modality of treatment of alcoholics Alcoholics Anonimous (A.A.) spread globally for so many years, arouses the interest of areas of knowledge for understanding the dynamics of this proposal. In the present work, we aim to investigate the relationship between personal accomplishment and community experience in the social-cultural context of the A.A. In order to learn the phenomenon in all its complexity and unit, we adopted the theoretical methodology orientation of classic Phenomenology. We used fundamental concepts of the phenomenological approach (intentional consciousness, epoché, phenomenological attitude) to understand the mutual constitution of person/life-world. We discuss about the human world in which the subject is inserted (life-world and culture), constitutive elements of the self person; process of formation and personal accomplishment, starting from the concepts of personal core and elementary experience; and the social grouping community favoring this process. We problematized the cultural contemporary model, characterized by multiples lifeworld and we approached the religious experience while meeting with a Being who vitalizes the person. To comprehend the A.A. context, we used a documental data collection and participant observation ethnographically. To carry out the semi-structured interviews, we intentionally selected subjects that held the customized speech about the A.A. that could indicate personal achievement. We asked that a key-informer indicate people that were considerate fulfilled in the A.A. to be interviewed. We used also other criteria to select the subjects: different participation time in the A.A. and different genders. We selected four interviews to the phenomenological analysis. Beginning from the way the subjects live the A.A., we learned essencial elements from the personal accomplishment experience in this social-cultural context, harvesting the dynamics of the relation person/community. We highlight that the subjects achieve themselves as they reassure their own lives and their alcoholic condition, from the encounter with the other, as overcoming models, whom welcomes and values them; they envision new ways of taking care of themselves and deal with tensions, living the experience of learning and personal growth from the sharing with the other and the elaborations of the social-cultural proposal of the A.A.; the attach each other in a communitarian way with the other participants of the A.A., living a solidarity and friendship relationship marked by giving oneself to another, contributing with the alien personal process; bringing to the alien process and caring with the community context of the A.A, building a world of networks, in and out of this reality, wich supports the recovery process; living a religious experience of relation with a divine Power which favors the self-care process. Given these results, we conclude that the experience of self-accomplishment in the A.A. is not expressed mainly by reproduction of formal principles in this context. For those who do the personal experience achievement in the social-cultural context of the A.A., it is favored by the proper apprehension of value in the official proposal in line with the personal quest for self care (enabling positioning of openness for the exam of the own experience and to te world), and also favored by the personal training of community ties in the A.A. that becomes the sustenance for the process of subjectivation and the achievement and maintenance of sobriety.